Efficacy of intraperitoneal lidocaine in gallbladder bed on pain management after laparoscopic cholecystectomy - معروف, علي; علي علوش; معن حيدر (Latakia University Journal -Medical Sciences Series, 2024)
Background: Laparoscopic cholecystectomy represents the main form of surgical interventions for cholelithiasis. Although it has some advantages regarding of early recovery and short hospital stays, it is not free of drawbacks such as postoperative pain which is considered one of the biggest healthy challenges. Aim: The purpose of this study was to investigate the effect of intraperitoneal instillation of lidocaine 2% for postoperative pain after laparoscopic cholecystectomy and the need for opioid analgesics. Materials and Methods: This was an analytical comparative Study (prospective) involving 100 patients who underwent laparoscopic cholecystectomy. They were selected from Department of General surgery, Tishreen University Hospital, Lattakia, during the period 2023-2024. Patients were randomly assigned into equal groups; lidocaine group(50 cases) and control group(50 cases) with comparison final outcome between two groups. Results: Out of 100 patients, 31 were males(31%) and 69 were females(69%). Mean age of the patients was 45.44±13.7 years and 66% of the patients were in group I according to ASA classification. There were no significant differences between two groups regarding of age, sex, body mass index(BMI), ASA classification, duration of surgery and anesthesia time(p>0.05). Frequency of postoperative shoulder pain, nausea and vomiting in lidocaine group versus control group were as follows;(88% vs. 96%,p:0.1), (38% vs.44%,p:0.5) and (20% vs. 24%,p:0.4) respectively. In addition to, need for analgesics was significantly less frequent in lidocaine group(92% versus 100%,p:0.04). Mean time of analgesic initiation was significantly longer in lidocaine group(4.5±1.5 hours vs. 2.92±0.8 hours in control group,p:0.001). Shoulder and abdominal pain scores were significantly lower in lidocaine group compared to controls during the first six hours after surgery(p<0.05). Conclusion: The current study demonstrated that intraperitoneal instillation of lidocaine is considered as an effective and safe method for pain management after laparoscopic cholecystectomy with reduction the need for analgesics.